THE ROLE OF BANKRUPTCY IN THE LIQUIDATION OF THE ASSETS OF THE ENTREPRENEUR OR THE UNVIABLE BUSINESS COMPANY (CIPEEX, 2025)
This paper analyzes bankruptcy, a legal institution regulated by Law No. 11.101/2005, which aims to liquidate the assets of an entrepreneur or an unviable business corporation, ensuring the satisfaction of creditors in a proportionate and orderly manner. The study adopts a bibliographic and doctrinal approach, examining the legislation and the understandings of legal experts specializing in Business Law. Bankruptcy is declared when a company proves unable to meet its financial obligations and is unable to recover, leading to judicial liquidation. In this process, the debtor's assets are seized, sold judicially, and converted into cash for later payment to creditors, following the legal order of preference. As Fran Martins, a classical scholar, teaches, bankruptcy should not be understood solely as a punishment for the entrepreneur, but as a necessary mechanism for protecting credit and ensuring security in economic relations. The results of the analysis indicate that, although bankruptcy represents the termination of business activities, it fulfills an essential function in market reorganization, as it removes unviable companies from the economic landscape and allows the circulation of assets to new economic agents. Thus, it is concluded that bankruptcy is an indispensable instrument for balancing the financial system and strengthening trust in business relationships.